MANAGEMENT CONTROL SYSTEM IN EDUCATIONAL INSTITUTIONS FROM THE LENSE OF IMPRINTING THEORY - Fitria, Pipit; Kusuma, Poppy Dian Indira (Among Makarti, 2024)
Abstract : This study aims to explore the influence of leaders on the creation of a blueprint which has an impact on the design and implementation of management control systems (MCS). Based on imprinting theory, organization founders and leaders often exhibit imprinting behavior. With his background and characteristics, a leader might create a blueprint for the organization he leads. This blueprint can influence the design and development of the MCS. A study in this area is important to provide insight into how leaders can contribute to an effective MCS implementation in an organization. This study uses a qualitative approach with a case study method conducted in SMK Persatuan Ummat Islam, located in Cirebon. Data were collected through in-depth interviews with relevant informants. Triangulation of information sources was also carried out to ensure data validity. The results of this study indicate that the leader instils the bureaucratic blueprint and influences the design and implementation of MCS in SMK Persatuan Ummat Islam in Cirebon. These results imply that the selection of leaders in an organization needs to be carried out in a planned and appropriate manner. Selecting a good leader who fits the organization's needs will create a good MCS and assist the organization in achieving its goal.Abstrak : Penelitian ini bertujuan untuk mengeksplorasi pengaruh pimpinan dalam penentuan blueprint pada suatu organisasi, yang berdampak pada desain dan implementasi Sistem Pengendalian Manajemen (SPM). Berdasarkan teori imprinting, para pendiri dan pemimpin organisasi seringkali menunjukkan perilaku imprinting. Dengan latar belakang dan karakteristiknya, seorang pemimpin bisa saja menciptkan blueprint organisasi yang dipimpinnya. Blueprint ini dapat mempengaruhi desain dan implementasi SPM dalam organisasi. Penelitian ini penting dilakukan untuk memberikan pemahaman bahwa pemimpin dapat mempengaruhi keefektivan implementasi SPM dalam sebuah organisasi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, yang dilakukan di SMK Persatuan Ummat Islam yang berlokasi di Cirebon. Data dikumpulkan melalui wawancara mendalam kepada informan yang relevan dengan penelitian ini. Triangulasi sumber informasi juga dilakukan untuk menjamin keabsahan data. Hasil penelitian ini menunjukkan bahwa blueprint birokrasi ditanamkan oleh pemimpin dan mempengaruhi desain dan implementasi SPM di SMK Persatuan Ummat Islam di Cirebon. Hasil ini memberikan implikasi bahwa pemilihan pemimpin dalam suatu organisasi perlu dilakukan secara terencana dan tepat. Pemilihan pemimpin yang baik dan sesuai dengan kebutuhan organisasi akan menciptakan SPM yang baik dan akan membantu organisasi dalam mencapai tujuannya.